Meningkatkan Hasil Belajar Pak Menggunakan Metode PBL Materi Aku Tumbuh dan Berkembang SDN 10 Cimpungan Kabupaten Mentawai Tuapejat - Pentinar Aritonang; Hartutik Hartutik; Sugiyana Sugiyana (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2025)
The problem of grade III students of SDN 10 Cimpungan is the lack of interest and understanding of students in the learning material. Students tend to feel bored and sleepy during the learning process, which leads to low learning outcomes. To overcome these challenges, interesting learning methods are needed to improve student learning outcomes and interest in the classroom. One method that has proven effective is Problem Based Learning (PBL). The purpose of this research is to improve learning outcomes and learning outcomes by applying the problem based learning (PBL) method of growing and developing materials. Focusing on the independence dimension of the Pancasila profile is intended to improve the cognitive/achievement aspect and affective/behavioral aspects of students. The class action research method was carried out in 2 cycles. This class action research was carried out on November 2 and 9, 2024 with four stages, namely: planning, implementation, evaluation, and reflection with 10 respondents, 3 women and 7 men. Data analysis was carried out with descriptive percentages to determine the increase in the aspect of student independence. The results of the first cycle of research on the cognitive aspect showed that 40% were proficient, 40% proficient 20%, with an average score of 78 cognitive aspects/learning achievements. In the second cycle, there was a significant increase in proficient 60%, proficient 30%, and only 10% developed, and the average observation learning outcomes reached 86.5%. The results of the reflection recommend that there needs to be assistance in the affective aspect so that it can increase students' learning independence. The implications of this finding confirm that the PBL method is able to increase students' independence and achievement targets in learning. The results of the first cycle of research to the second cycle of cognitive aspects showed an increase of 30% with a score of 86-100 in the advanced category of 30%, 40% with a score of 75-85 in the proficient category and 20% with a score of 60-74 in the feasible category, 10% with a score of 0-59 in the undeveloped category. Meanwhile, the data from the final evaluation of cycle 2 shows that 50% of the advanced category, 40% of the capable category, 10% of the feasible category and none of those in the category have not developed so that the percentage is also 0%. Meanwhile, the average results of the affective value of the independence aspect: activeness obtained a score from 60% to 85%, ability to complete tasks from 30% to 88%, ability to analyze from 10% to 82%, and creativity from 40% to 80%.